A Review: Contact Electrification on Special Interfaces - Zhang, Wenhao; Shi, Yuxiang; Li, Yufang; Chen, Xiangyu; Shen, Honglie (Frontiers in Materials, 2022)
The contact electrification of materials plays an important role in developing and applying triboelectric nanogenerators (TENGs). By exploring the contact electrification phenomena at different interfaces, we can improve the understanding of the electrification mechanism and expand the application field of TENGs. In this way, the rate of energy utilization can be improved while the harm caused by the electrostatic effect is reduced. This article systematically summarized the different interface contacts between the research status quo of electricity. This article expounds the solid–solid interface, liquid–solid interface, and liquid–liquid interface, as well as the gas and other interface contact electrification mechanism, and the research and application of these are introduced; finally, it prospects the contact between the different interfaces of electric potential applications as well as the challenge.